Stepwise‐clustered heatwave downscaling and projection for Guangdong Province - Jiayan Ren; Guohe Huang; Yongping Li; Xiong Zhou; Chen Lu; Ruixin Duan (International Journal of Climatology, 2022)
Heatwave events over Guangdong have attracted recent attention under changing climate conditions. It is desired to explore the future changes of heatwave due to its associated consequences on society economy and environment. In this study, a stepwise‐clustered heatwave downscaling approach (i.e., SCHW) was developed for the projection of HWs in Guangdong. The heatwave indicators (occurrence, duration, magnitude, intensity, frequency, and accumulated intensity) were investigated from both the absolute and relative definitions of heatwave events (i.e., AHWs and RHWs) based on the multi‐model ensemble of 13 coupled model intercomparison projected phase 5 (CMIP5) global climate models (GCMs) under two representative concentration pathways (RCPs). The trends (i.e., 0.18–0.29°C per decade under RCP4.5 and 0.30–0.58°C per decade under RCP8.5) of the projected daily maximum temperature indicate that Guangdong would experience continuous warming in the future. The occurrence, frequency, and accumulated intensity of heatwave would increase by 198%, 272%, and 346% in the 2080s (i.e., 2066–2095) under RCP8.5 compared to the historical period (i.e., 1976–2005), respectively. Moreover, the three indicators of HWs are projected to have more substantial increases over inland Guangdong than its costal parts. The spatial variation of occurrence of absolute and relative heatwave under RCP8.5 (2.80 and 2.78) is larger than these under RCP4.5 (2.50 and 2.32) during 2080s (i.e., 2066–2095). The projections of future HWs can help provide valuable information for assessing extreme climate change and identifying desired adaptation strategies.